Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease - Joshi, Rakesh S.; Jagdale, Shounak S.; Bansode, Sneha B.; Shankar, S. Shiva; Tellis, Meenakshi B.; Pandya, Vaibhav Kumar; Chugh, Anita; Giri, Ashok P.; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infection. The main protease (M-Pro) plays a critical role in viral replication and maturation, thus can serve as the primary drug target. To understand the structural evolution of M-Pro, we have performed phylogenetic and Sequence Similarity Network analysis, that depicted divergence of Coronaviridae M-Pro in five clusters specific to viral hosts. This clustering was corroborated with the comparison of M-Pro structures. Furthermore, it has been observed that backbone and binding site conformations are conserved despite variation in some of the residues. These attributes can be exploited to repurpose available viral protease inhibitors against SARS-CoV-2 M-Pro. In agreement with this, we performed screening of similar to 7100 molecules including active ingredients present in the Ayurvedic anti-tussive medicines, anti-viral phytochemicals and synthetic anti-virals against SARS-CoV-2 M-Pro as the primary target. We identified several natural molecules like delta-viniferin, myricitrin, taiwanhomoflavone A, lactucopicrin 15-oxalate, nympholide A, afzelin, biorobin, hesperidin and phyllaemblicin B that strongly binds to SARS-CoV-2 M-Pro. Intrestingly, these molecules also showed strong binding with other potential targets of SARS-CoV-2 infection like viral receptor human angiotensin-converting enzyme 2 (hACE-2) and RNA dependent RNA polymerase (RdRp). We anticipate that our approach for identification of multi-target-directed ligand will provide new avenues for drug discovery against SARS-CoV-2 infection. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; COVID-19; hACE-2; MPro; multi-target-directed ligand; protease inhibitor; RdRp; SARS-CoV-2 virus

Antiviral drugs prioritization for COVID-19 management based on rational selection - Joshi, Rakesh S.; Giri, Ashok P.; Kulkarni, Mahesh J.; Gupta, Mahesh; Verma, Savita; Chaudhry, Dhruva; Deshmukh, Narendra; Chugh, Anita (Current Science, 2021)
The SARS-CoV-2 infection has resulted in COVID-19 pandemic worldwide. It has infected around 0.1 billion individuals and caused 2 million fatalities across the globe till mid-January 2021. Drug repurposing has been utilized as the most preferred therapeutic intervention for COVID-19 mitigation due to its necessity and feasibility. To prioritize therapeutic regime against COVID-19, we used 61 antiviral drugs and their combinations. Selected molecules were subjected to virtual screening against: (i) human angiotensin-converting enzyme 2 receptor binding domain (hACE-2) which serves as an anchor for virus attachment and entry, (ii) SARS-CoV-2 RNA dependent RNA polymerase (RdRp) responsible for viral RNA replication, and (iii) SARS-CoV-2 main protease (M-Pro) needed for viral polyprotein slab proteolytic processing. Based on docking score, pharmacodynamic and pharmacokinetic parameters, combinations of Daclatasvir, Elbasvir, Indinavir, Ledipasvir, Paritaprevir and Rilpivirine were analysed further. Our analysis suggested Sofosbuvir in combination with Ledipasvir and Daclatasvir as potential therapeutic agents for SARS-CoV-2. The combined score suggests that these combinations have superior anti-SARS-CoV-2 potential than Remdesivir and other investigational drugs. The present work provides a rationale-based approach to select drugs with possible anti-SARS-CoV-2 activity for further clinical evaluation.
Keywords: Drug repurposing; hACE-2; main protease; RNA dependent RNA polymerase; SARS-CoV-2